Els cants singulars i particulars del gradual de Sant Romà de les Bons = Els cants singulars i particulars del gradual de Sant Romà de les Bons, The unique and particularly interesting chants of the gradual of Sant Romà de les Bons - Orio, Francesco (Miscel·lània litúrgica catalana, 2024)
The manuscript E-Bbc ms. 1805, dating back to the first half of the 12th century, is a gradual of the Franco-Roman rite with late semi-diastematic Catalan-Narbonese neumatic musical notation. It was discovered in the church of Sant Romà de les Bons in Andorra, along with the codices E-MO ms. 838 and E-MO ms. 72, and is now housed in the Biblioteca de Catalunya. This paper presents a thorough examination that follows up and expands upon the previous study published in Vox Antiqua, 20 (2022) entitled "Studio sulla notazione catalano-narbonese" ("Study on Catalan-Narbonesenotation"). The unique chants in the manuscript and those deserving particular attention are analyzed, especially including the unique alleluiatic verses, an offertory, a verbeta, two additions, and other particular pieces. Together with some musical and liturgical features, the evidence suggests a probable French origin of the manuscript – contrary to the Urgell tradition put forward in the bibliography.